The effect of international accreditations on students' revealed preferences: Evidence from French Business schools. (December 2021) - Jacqmin, Julien; Lefebvre, Mathieu
Abstract: This paper evaluates how three different international accreditations for business schools (AACSB, EQUIS and AMBA) affect student preferences, expressed via enrollment decisions. Focusing on the French context, we build a relative preference indicator to compare schools using data collected by the central clearinghouse that allocates students to schools. We observe that all three accreditations positively and significantly influence students, but that the impact of the AACSB accreditation is larger than the other two accreditations. Having an AACSB accreditation is equivalent to moving up four places in rankings by L'étudiant magazine, whereas the impact of having EQUIS or AMBA is similar to moving up two places. We also find a sizeable "triple crown" effect, meaning that the three accreditations tend to complement each other. Our results are robust to different ways of assessing potential self-selection into accreditation.